Educação ambiental e valores: sentidos construídos por professores em formação continuada - Jordão, Thalita [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Against the environmental crises we face, we believe that the current education system has been pointed out as one of the most important socials manner to face such problems. Since it can encourage changes on our values, on our conceptions and, consequently, on our actions. This way we can correcting, minimizing, or even reverting a lot of environmental impacts. Supported by a criticism environmental education and focusing on the work with the values dimension of environmental education, we turn to the figure of the teacher, central element for school colaborate with changing desired. The goal of our research is the understanding of senses built by teachers involved in forming program offered by UNESP of Rio Claro, focused to the environmental education and their evaluative dimensions. We focus on reflective texts twenty teachers of different subjects from the public school system, written over the continuing education program occurred in 2013. Through a qualitative analysis, we appeal to bakhtiniano referential which gives privilege to relations as analysis places and signification production. The research was stablished from lectures of built thoughts of teachers in 2013 and followed to the identification of central ideas (a pointer). The built thoughts went through an interpretation of senses and they were classified into empiric categories or kernel senses, giving us description of themes as abroad classification. During the comprehension processes arises five senses: the sense of limited vision, the sense of doubt, the sense of to effort, sense of the challenge and the awakening of discovering/novelty. This experience reflectes an urgency for new practices in the class, because it was possible to find out that formed continuation education makes propitious space for establishment of dialog and further very important and significant changes of experiences between theory and practical knowing. The program attended by the participants...

Diante da atual crise ambiental o processo educativo, tem sido apontado como uma das práticas sociais com possibilidades de enfrentamento desta problemática, estimulando uma mudança de valores, concepções e ações que podem minimizar corrigir ou até mesmo reverter as situações de impacto ambiental. Apoiadas na educação ambiental crítica e focando o trabalho com a dimensão valorativa da educação ambiental, nos voltamos para a figura do professor, elemento central para que a escola colabore com a mudança almejada. Isso nos levou a investigar a formação docente. O objetivo de nossa pesquisa é o de compreender os sentidos construídos pelos professores envolvidos em um programa formativo, voltado à educação ambiental e sua dimensão valorativa. Focamos nos textos reflexivos de vinte professores de diferentes disciplinas da rede pública de ensino, escritos ao longo do programa de formação continuada ocorrido no ano de 2013. Por meio de uma análise qualitativa, recorremos ao referencial bakhtiniano que privilegia as relações como lugar de análise e produção de sentido. A pesquisa caminhou para a identificação das ideias centrais (indicadores), passou pela interpretação dos sentidos dessas ideias e pelo agrupamento dessas ideias em categorias empíricas ou núcleos de sentido, chegando-se assim, na descrição de temas, como classificações mais amplas. Durante o processo de compreensão emergiram cinco sentidos relativos aos trabalhos realizados por eles: o sentido de visão limitada, o sentido da dúvida, o sentido do esforço, o sentido do desafio e o desabrochar do sentido da novidade/descoberta. Esta experiência refletiu a emergência de novas práticas educativas, pois, foi possível constatar que a formação continuada, promoveu espaços propícios para estabelecer diálogos e promover trocas muito importantes e significativas entre a teoria e a prática. O programa frequentado pelos participantes dessa...
Keywords: Educação ambiental; Professores - Formação; Valores